Pengaruh Persepsi Atas Kompetensi Pedagogik Guru dan Lingkungan Belajar Terhadap Prestasi Belajar Bahasa Indonesia (Survei pada SMP Swasta di Wilayah Jakarta Utara) - Abdullah, Farid Wajedi; Sumaryoto, Sumaryoto; Dja'far, Harmi Ibnu (Universitas Indraprasta PGRI, 2024)
The aim of this study is to find out 1) The influence of perceptions of teacher pedagogical competence and the learning environment on Indonesian language learning achievement of private junior high school students in the North Jakarta region 2) The influence of perceptions of teacher pedagogical competence on Indonesian language learning achievement of private junior high school students in the North Jakarta region 3) The influence of the learning environment towards learning achievement on Indonesian language learning of private Junior High School students in North Jakarta region. This study is conducted using a survey method with correlational techniques. The sample of this study is 60 students chosen disorderedly. The result of this study represents that 1) There is a significant influence of perceptions of teacher pedagogical competence and the learning environment together on the Indonesian language learning achievement of private junior high school students in the North Jakarta region. It is evidenced by the acquisition of Sig = 0.028 < 0.05 and Fcount = 1.519. 2) There is a significant influence of perceptions of teacher pedagogical competence on the Indonesian language learning achievement of private junior high school students in the North Jakarta region. It is evidenced by the acquisition of Sig = 0.002 < 0,05 dan tCount= 0.818. There is a significant influence of the learning environment on the Indonesian language learning achievement of private junior high school students in the North Jakarta area. It is evidenced by obtaining a value of Sig = 0.000 < 0.05 and tcount = 1.470.